1999
DOI: 10.1084/jem.190.10.1375
|View full text |Cite
|
Sign up to set email alerts
|

A Proinflammatory Cytokine Inhibits P53 Tumor Suppressor Activity

Abstract: p53 has a key role in the negative regulation of cell proliferation, in the maintenance of genomic stability, and in the suppression of transformation and tumorigenesis. To identify novel regulators of p53, we undertook two functional screens to isolate genes which bypassed either p53-mediated growth arrest or apoptosis. In both screens, we isolated cDNAs encoding macrophage migration inhibitory factor (MIF), a cytokine that was shown previously to exert both local and systemic proinflammatory activities. Trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
441
3
12

Year Published

2000
2000
2010
2010

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 583 publications
(470 citation statements)
references
References 42 publications
14
441
3
12
Order By: Relevance
“…[20][21][22] Several studies have indicated that activation of cell proliferation by MIF is due to a functional inactivation of the p53 tumor suppressor. 17,18,23 Thus, MIF overexpression extends the lifespan of primary cells in vitro, inhibits Myc-induced p53-dependent apoptosis, and protects macrophages from NO-induced apoptosis. 17 Conversely, when MIF is lost, cell survival and functions are compromised in a p53-dependent manner.…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…[20][21][22] Several studies have indicated that activation of cell proliferation by MIF is due to a functional inactivation of the p53 tumor suppressor. 17,18,23 Thus, MIF overexpression extends the lifespan of primary cells in vitro, inhibits Myc-induced p53-dependent apoptosis, and protects macrophages from NO-induced apoptosis. 17 Conversely, when MIF is lost, cell survival and functions are compromised in a p53-dependent manner.…”
Section: Introductionmentioning
confidence: 97%
“…17,18,23 Thus, MIF overexpression extends the lifespan of primary cells in vitro, inhibits Myc-induced p53-dependent apoptosis, and protects macrophages from NO-induced apoptosis. 17 Conversely, when MIF is lost, cell survival and functions are compromised in a p53-dependent manner. 17,18 It has been proposed that this functional suppression of p53 by MIF is based on interference with p53-dependent transcriptional activity.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations